Code-Mixing as an Epistemological Strategy in Arabic Semantic Learning: An Ethnopedagogical Study in Indonesian Higher Education - Damhuri Damhuri; Ratni Bt. Hj. Bahri; Mukhtar I. Miolo; Taj Rijal bin Muhamad Romli; Kaharuddin Ramli (Jurnal Ilmiah Peuradeun, 2026)
The growing emphasis on culturally responsive pedagogy has highlighted the need to integrate indigenous knowledge into language education; however, limited attention has been given to how local cultural values can function as epistemological resources in Arabic semantic learning. This study examines how code-mixing serves as an epistemological strategy for connecting Arabic semantic concepts with the indigenous values of Gorontalo, Indonesia, namely tulodu (exemplary conduct), lo lipu (social affection), and momuliyo (dignified patience). Employing a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews, focus group discussions, and document analysis involving Arabic language lecturers and undergraduate students at an Islamic higher education institution. The data were analyzed using an integrated framework combining Muysken’s code-mixing typology, contextual semantics, and ethnopedagogical principles. The findings reveal that code-mixing functions not merely as a linguistic practice but as a pedagogical and epistemological mechanism that contextualizes meaning, facilitates semantic comprehension, and promotes moral and cultural internalization. By linking abstract Arabic concepts with culturally familiar references, learners develop deeper cognitive, affective, and reflective engagement with language. The study contributes to the advancement of multilingual education and ethnopedagogical scholarship by demonstrating how indigenous knowledge can enrich semantic learning and offers a culturally grounded model for language education in multicultural and religiously diverse contexts.